2008
DOI: 10.1038/ejhg.2008.176
|View full text |Cite
|
Sign up to set email alerts
|

PTCH1 duplication in a family with microcephaly and mild developmental delay

Abstract: With the exception of the X chromosome, genomic deletions appear to be more prevalent than duplications. Because of a lack of accurate diagnostic methods, submicroscopic duplications have been under-ascertained for a long period. The development of array CGH has enabled the detection of chromosomal microduplications with nearly the same sensitivity as deletions, leading to the discovery of previously unrecognized syndromes. Using a clinical targeted oligonucleotide array (CMA-V6.3 OLIGO), we identified an B360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…Genetic studies/genome scans have revealed mutations in some patients with autism- associated symptoms. These genetic changes affect the transmission of both, GABA- and glutamatergic synapses (Hussman, 2001; Jamain et al, 2002; Derwińska et al, 2009, reviewed by Rubenstein and Merzenich, 2003; State, 2010). Reduced GABAergic signaling of interneurons of the L and BL nuclei might yield a “hyperexcitability-state” of the respective nuclei as found by Markram et al (2008) and reviewed by Markram and Markram (2010) in the rat-valproic acid-model of autism and in consequence impair both intraamygdaloid and amygdalo-cortical circuitry.…”
Section: Stimulation Sitesmentioning
confidence: 99%
“…Genetic studies/genome scans have revealed mutations in some patients with autism- associated symptoms. These genetic changes affect the transmission of both, GABA- and glutamatergic synapses (Hussman, 2001; Jamain et al, 2002; Derwińska et al, 2009, reviewed by Rubenstein and Merzenich, 2003; State, 2010). Reduced GABAergic signaling of interneurons of the L and BL nuclei might yield a “hyperexcitability-state” of the respective nuclei as found by Markram et al (2008) and reviewed by Markram and Markram (2010) in the rat-valproic acid-model of autism and in consequence impair both intraamygdaloid and amygdalo-cortical circuitry.…”
Section: Stimulation Sitesmentioning
confidence: 99%
“…In addition to the comprehensive and quick characterisation of this new duplication, we have used array-CGH technology which provides both high-resolution and sensitivity to characterise copy-number variations [16,11]. The analysis showed a duplication of about 70 kb (proximally: last normal oligo 116,948,976 Mb, first duplicated one 116,963,849 Mb; distally: last duplicated oligo 117,030,994 Mb, first normal one 117,039,020 Mb) harbouring no less than 9 exons when considering the internal edges of the duplication (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that some patients with Fanconi anemia presented with pre‐ and postnatal growth retardation, microcephaly, and short stature (Giampietro et al, ; Joenje and Patel, ), suggesting that duplication of FANCC might contribute to the phenotypic features of the partial trisomy 9q syndrome. Derwińska et al () suggested that gain‐of‐function or duplication of PTCH1 was responsible for the microcephaly with or without holoprosencephaly. This is supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Rotthier et al () reported a SPTLC1 mutation in a French Gypsy patient with severe growth retardation, ID, and microcephaly. Derwińska et al () reported a 364‐kb duplication encompassing the entire PTCH1 gene in a mother and son with microcephaly and mild DD. Finally, patients with BICD2 mutations have not been described with a phenotype similar to the one observed in our patient.…”
Section: Discussionmentioning
confidence: 99%